Pioneer Centre the link for urban regeneration - Dee, Tristan Samuel T.
Urbanization is one phenomena that creates good and bad outcomes in a community. It can be seen as a driver for economic growth and competitiveness but also creates strain on infrastructure, utilities and services, environment, and land use. Pasig City is currently experiencing this urbanization specifically within the Pasig City Business District and its surrounding areas. One area that is greatly changing because of this is Brgy. Kapitolyo. A once residential neighborhood is now becoming a highly urbanized area. With this, residents are experiencing a physical and social disconnect of the 'old' and 'new' Brgy. Kapitolyo. The project aims to bridge the physical and social disconnect of the 'old' and 'new' Brgy. Kapitolyo through the redevelopment of Pioneer Centre, as well as to improve the sense of place of the residents by providing an urban center that fosters informal and formal interactions. The redevelopment of Pioneer Centre was done through the Connected Community Approach that involves the inputs of key stakeholders as a guide for the design process. Ultimately the project is an example of a community-based design that strengthens the sense of place and connect of the community for years to come.